Ultrasound and Carcass Merit of Youth Market Hogs - Chad Carr; Dwain Johnson; Mark Shuffitt (EDIS)
AN252, a 5-page illustrated fact sheet by Chad Carr, Dwain Johnson, and Mark Shuffitt, describes the process whereby ultrasound evaluation of the live animal can be used to predict fat thickness and loineye area to determine the carcass merit of youth market hogs. Includes references. Published by the UF Department of Animal Science, October 2010.